2019
DOI: 10.1101/720904
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic control of tracheid properties in Norway spruce wood

Abstract: 16 Through the use of genome-wide association (GWAS) mapping it is possible to 17 establish the genetic basis of phenotypic trait variation. Our GWAS study presents the 18 first such an effort in Norway spruce (Picea abies (L). Karst.) for the traits related to 19 wood tracheid characteristics. 20  The study employed an exome capture genotyping approach that generated 178 101 21 high quality Single Nucleotide Polymorphisms (SNPs) from 40 018 probes within a 22  The results demonstrate feasibility of GWAS to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 94 publications
0
1
1
Order By: Relevance
“…For example, Elfstrand et al (2020), performing GWAS for disease resistance traits in Norway spruce using 466 genotypes, did not find any overlapped SNPs with another previous study using 66 genotypes/clones (Mukrimin et al, 2018). We also did not observe the same QTLs detected in two previous studies of Norway spruce using a smaller population (517 trees) (Baison et al, 2019(Baison et al, , 2020. In this study, we performed GWAS analysis in a parental population (476 trees) and identified nine SNPs with p < 0.05 that overlapped with the associated SNPs in the GWAS of their progenies (Table 3).…”
Section: E Ect Of Population Size and Heritability On Gwascontrasting
confidence: 56%
See 1 more Smart Citation
“…For example, Elfstrand et al (2020), performing GWAS for disease resistance traits in Norway spruce using 466 genotypes, did not find any overlapped SNPs with another previous study using 66 genotypes/clones (Mukrimin et al, 2018). We also did not observe the same QTLs detected in two previous studies of Norway spruce using a smaller population (517 trees) (Baison et al, 2019(Baison et al, , 2020. In this study, we performed GWAS analysis in a parental population (476 trees) and identified nine SNPs with p < 0.05 that overlapped with the associated SNPs in the GWAS of their progenies (Table 3).…”
Section: E Ect Of Population Size and Heritability On Gwascontrasting
confidence: 56%
“…Norway spruce (Picea abies) is the most important commercial tree species in Northern Europe. GWAS has been conducted for several wood properties using 517 Norway spruce individuals (Baison et al, 2019(Baison et al, , 2020. SNPs have been identified for the traits of wood density, stiffness, the number of cells, and cell wall thickness.…”
mentioning
confidence: 99%